THE EFFECT OF DIET AND PELLET SIZE ON THE PASSAGE RATE OF FEED IN THE DIGESTIVE TRACT OF BROILER CHICKENS - Burhanudin SUndu (Universitas Tadulako, 2008)
An experiment was carried out to determine the rate of intestinal passage of a pelleted copra meal based diet compared to that of a pelleted corn-soy based diet both ground to different pellet sizes. A total of 64 male broiler chickens of six weeks of age were used in this trial. The birds were kept in cages equipped with a trough feeder and drinker. On day 1 to 5, the birds were fed the experimental diets. On day 6, after a 12 h feed restriction, all birds were orally administered with 85 mg chromium oxide in a gelatine capsule. Four birds per treatment were killed by cervical dislocation. Gizzard and small intestine were opened and the colour of the digesta observed to visually determine the location of the chromium oxide. The faeces were observed for first appearance of entire coloured faeces and then on an hourly basis up to the disappearance of coloured faeces. The experimental design was a two way factorial with two basal diets and pellet sizes. Data indicated that a copra meal diet moved in the digestive tract slower than a corn-soy diet. The first appearance of the marker in the faeces of birds fed the copra meal diet was 52 minutes later than for those fed the corn-soy diet. The movement in the digestive tract of the fine ground diets was slower than that of the coarse diets. The effect of pellet size on feed passage time was only evident in the copra meal based diet.